A modified pi-shaped circuit-based model of grounding electrodes - Yutthagowith, P. (My University, 2016)
This paper proposes a modified pi-shaped circuitbased model of grounding electrodes. The validity length and soil resistivity of the proposed model are from 2 m to 40 m and from 50 m to 2000 m, respectively. The equivalent circuits in the form of pi configuration are modeled by lumped parameters composing of inductance, resistances, and capacitances. The voltage responses to the standard lightning currents of grounding electrodes either calculated by an electromagnetic model or from experiments are matched with those of the proposed model. A curve fitting technique is employed to extract parameters of the equivalent circuit. The satisfactory agreements have been observed. The simple soil ionization model can readily be adapted in the proposed model. The proposed model is very useful in implementation with a circuit simulator such as EMTP, Pspice, and so on. The proposed circuit model can be adapted for being the models for development and design of the grounding system for lightning protection system in transmission and distribution systems in an effective way.
Keywords: Electrical transient; Equivalent circuit; Grounding electrodes; Lightning current; Modified pi model; Soil ionization